Grape seed proanthocyanidin extract alleviates arsenic-induced lung damage through NF-κB signaling. Issue 3 (March 2019) - Hu, Yunhua; Wei, Meng; Niu, Qiang; Ma, Rulin; Li, Yu; Wang, Xianhua; Feng, Gangling; Li, Shugang; Pang, Lijuan
Proanthocyanidin has beneficial features such as free radical scavenging, anti-inflammation, and anti-oxidation. There is no study on whether proanthocyanidin could protect against arsenic-induced respiratory inflammatory damage. The aim of the study is to examine the anti-inflammatory effects of proanthocyanidin and the molecular mechanisms in vivo and in vitro. BEAS-2B cells were treated with As2 O3, grape seed proanthocyanidin extract (GSPE), and/or BAY 11–7082. Kunming mice were treated with As2 O3 and/or GSPE. p-IκB-α, IκB-α, IKKα/β, NF-κBp65, and NF-κBp50 were assessed by Western blot and qRT-PCR. Lung histology was examined. Arsenic affected the histology of the mouse lungs, but GSPE attenuated those effects. As2 O3 increased cell apoptosis, which was reversed by GSPE. In cells and mouse lung tissue, arsenic increased the expression of IL-1β, IL-6, tumor necrosis factor-α, and C-reactive protein, and these effects were attenuated by GSPE. In cells and mouse lung tissue, arsenic enhanced the mRNA and protein levels of IKKα, IKKβ, NF-κBp65, and NF-κBp50, while the IκB-α levels were decreased compared with controls. IKKα, IKKβ, NF-κBp65, and NF-κBp50 mRNA and protein levels in the As2 O3 +GSPE groups were lower and IκB-α levels were higher than that in the arsenic groups. Arsenic-activated NF-κB signaling induced inflammatory damage through the upregulation of pro-inflammatory cytokines and downregulation of anti-inflammatory cytokines. GSPE plays a beneficial role against arsenic-induced inflammatory damage through, at least in part, the suppression of the arsenic-induced NF-κB signaling pathway. Impact statement: Arsenic-induced respiratory inflammatory damage is an important occupational hazard in many areas of the world, particularly in underdeveloped and developing countries. Effective treatments are lacking and expensive. Therefore, the aim of the study was to examine the anti-inflammatory effects of proanthocyanidin (PC) and the molecular mechanisms in vivo and in vitro. The present study showed that PC extracted from grape seed could attenuate the lung damage in a mouse model of arsenic poisoning. The effects were observed at the level of lung histology and inflammasome expression. This study suggests that a natural compound is effective in mitigating the toxic effects of arsenic in the lungs, providing an inexpensive and more readily accessible method for treating arsenic exposure in some parts of the world.